Circular economy and re-commerce in the fashion industry - Shrivastava, Archana, 1968-; Jain, Geetika, 1983-; Paul, Justin (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines best practices for assessing the technological landscape and for modelling sustainable business practices in the fashion industry"--